MTA2/NuRD as a regulator of NF-kB signalling in lung cancer progression - El-Nikhely, Nefertiti; Justus Liebig University Giessen (My University, 2016)
Inflammation and cancer have been linked more than a century ago when Rudolf Virchow identified leukocytes infiltration in neoplastic tissues. Many years of research followed until the discovery of NF-kB, which paved the way to more insight into the contribution of inflammatory signalling to cancer development. NF-kB is not only involved in many innate and adaptive immune responses but also governs the expression of wide set of diverse genes regulating cell growth and adhesion, cell cycle regulation, apoptosis, angiogenesis all established hallmarks of neoplastic transformation. Many tumours, especially solid tumours, exhibit constitutive activation of NF-kB canonical signalling pathway. This fact encouraged several researchers to develop NF-kB inhibitors and IKK2 inhibitors as adjunct therapy to existing cancer treatment modalities, however, with modest success. More studies are required for a better understanding of NF-kB activation in cancer and the underlying regulatory mechanisms.In this work, NF-kB canonical signalling was studied in lung adenocarcinoma cell lines and animal model. Chemical stimulation of various adenocarcinoma cells lines (A549, A427, Colo699, H1650, and H2122) as well as non-tumour cell lines (BEAS-2B and HEK) with LPS and TNFalpha induced NF-kB nuclear translocation and subsequent activation. The functional effects of NF-kB activation were reflected in increased proliferation and migration. Specific IKK2 inhibitors like sc-514, parthenolide or Bay11-7085 as well as proteosomal inhibitor like MG-132 showed opposed effects indicating that the pivotal role of IKK2 activation in cancer cells. In corroboration, genetic mouse model where IKK2 was specifically constitutively activated or downregulated in SPC-expressing epithelial alveolar type II cells (SpCrtTA/Tet-O-IKK2CA/SpC Ca-Raf BxB and SpCrtTA/Tet-O-IKK2DN/SpC Ca-Raf BxB, respectively) led to significant alterations in tumour development. Downregulation of IKK2 decreased the tumour dispersion in the lung and improved lung function. Furthermore, IKK2 changes in host epithelial cells also affected the immune cell repertoire significantly in the tumour microenvironment.Importantly, mouse epithelial alveolar type II cells expressing IKK2DN compared to wildtype cells regulated several genes that didn t possess any known NF-kB consensus sequences in their promoters. Among these genes was metastasis-associated protein family member 2, known as MTA2. Further examination of MTA2 expression on protein level in different cells lines suggested that cell lines originating from metastatic sites showed higher expression of MTA2 than those isolated from primary sites. Surprisingly, MTA2 was not upregulated in response to NF-kB stimulation, but regulated in response to IKK2 downregulation (IKK2DN or IKK2 inhibitor treatment).MTA2 is reported as a member of the NuRD complex (consisting of MBD1/2, HDAC1/2, CHD3/4, GATA2Da/b, and RbAp46/448) that regulates gene expression at a transcriptional level. Indeed, MTA2 overexpression decreased NF-kB activity and the expression of a wide set of NF-kB target genes. Interestingly, our results indicated the presence of MTA2 together with other members of the NuRD complex and NF-kB heterodimer p50/p65 as assessed by fractionation, immunoprecipitation and proximity ligation assay studies. Finally, ChIP assay could identify MTA2 and RbAp46 in the promoter region of NFKB1 and NFKBIA, a target gene of NF-kB. These data taken together support the hypothesis that MTA2 as part of NuRD complex binds to NF-kB and its target genes to regulate their expression.Finally, MTA2 was knocked down in LLC1 cells via shRNA and injected into C57Bl/6J mice subcutaneously. Tumours with shMTA2 were bigger in size compared to tumours from LLC1 control or even to LLC1-IKK2CA. Even their immune repertoire shifted towards a tumour-favouring signature with more M2-like macrophages and less cytotoxic T-lymphocytes.In summary, this work suggests MTA2 as regulator of NF-kB signalling pathway in lung cancer. Increased NF-kB activity leads to the expression of several cytokines that continue activating the pathway. A poised mechanism to tightly regulate NF-kB recruits MTA2/NuRD complex to cardinal NF-kB target genes repressing their transcription. The proposed mechanism still needs more research to elucidate the exact kinetics of this feedback loop regulation.

Seit dem letzten Jahrhundert, als Ruldof Virchow Leukozyten in Tumoren entdeckt hat, werden Tumorbildung und Entzündungsprozessen zusammengeknüpft. Viele Jahre der Forschung folgten bis zur der Entdeckung von NF-kB. Nuklear Faktor kappa B (NF-kB) ist ein wichtiger Transkriptionsfaktor für das Immunsystem und die Regulation von Entzündungsprozessen. Es gibt bereits mehrere Publikationen, die die Dysregulation von NF-kB in unterschiedlichen Krebsarten zeigen. Dennoch fehlt der Mechanismus dieser Regulation, der vor allem durch die aktivierende Kinase IKK2 (Inhibitor kappa B kinase beta) vorgeht.In der vorliegenden Arbeit wurde der klassische Signalweg von NF-kB in Lungenkrebs-Zelllinien und anhand von Tiermodellen untersucht. Chemische Stimulation der Tumor-Zelllinien (A549, A427, Colo699, H1650, und H2122) als auch der Kontrollzelllinien (BEAS-2B and HEK) durch LPS und TNFalpha führte zur Translokation von p50/p65 zum Zellkern. Die darauf folgende Aktivierung der Transkription verschiedener Gene spiegelte sich in zunehmender Proliferation und Migration der Zellen. Spezifische IKK2 Inhibitoren wie sc-514, parthenolide, Bay11-7085 und MG-132 haben diesen Prozess gehemmt. Diese Ergebnisse wurden in einem Tiermodell bestätigt, wo modifiziertes IKK2 unter dem SPC Promotor zusammen mit C-Raf BxB in alveolaren Epithelzellen exprimiert wurde (SpC rtTA/Tet-O-IKK2CA/SpC C-Raf BxB and SpC rtTA/Tet-O-IKK2DN/SpC C-Raf BxB). Die Runterregulation von IKK2 beschränkte die Tumorbildung, wie durch MRT und histologische Untersuchung zu erkennen war, und verbesserte damit die Lungenfunktion. Darüber hinaus haben die Veränderungen in IKK2-Aktivierung die Immunzellpopulation der Tumorumgebung beeinflusst.Maus Epithelzellen (ATII) wurden aus Wildtyp-Tieren und SpC rtTA/Tet-O-IKK2DN-Tieren isoliert. Durch den Vergleich der unterschiedlich exprimierten Gene wurde eine Gruppe von Genen identifiziert, die von IKK2DN beeinflusst wurden, obwohl sie keine NF-kB Konsensus-Sequenz erweisen. MTA2, metastasis-associated protein family member 2, gehörte zu dieser Gruppe.Andere Studien haben gezeigt, dass MTA2 in Nichtkleinzelligem Lungenkrebs hochreguliert wird und mit den Krebsstadien korreliert. Die Protein-Expression von MTA2 war in den Lungenkrebs-Zelllinien, die aus Metastasen stammen, höher exprimiert als in den Zelllinien, deren Herkunft Primärtumore ist. MTA2 gehört zu dem NuRD (Nucleosome Remodelling Deacetylase)-Komplex. Dieser Komplex besteht aus mehreren Proteinen, u.a. die MTA (Metastasen-assoziierten Proteinen)-Familie (MTA1, MTA2 oder MTA3). In der vorliegenden Studie wurde gezeigt, dass MTA2 Überexpression eine repressive Wirkung auf einige NF-kB-Zielgene ausübt. Außerdem wurde eine Interaktion zwischen p50/p65 und MTA2/NuRD durch Immunoprecipitation, PLA (proximity ligation assay) und die Fraktionierung nuklearer Komplexe bestätigt. ChIP-Experimente wiesen MTA2 und RbAp46 in den Promotorregionen von NFKB1 und NFKBIA (bekannte NF-kB-Zielgene) nach. Dies unterstützt unsere Hypothese, dass MTA2/NuRD-Komplex NF-kB-Zielgene reguliert.Zum Schluss wurden LLC1 Zellen, die shMTA2 und IKK2CA exprimieren, in subkutanem Tumormodell injiziert. Tumore mit blockierten MTA2 (shMTA2) waren mächtiger und zeigten eine tumorfördernde Immunzellumgebung.Zusammenfassend schlägt die vorliegende Arbeit MTA2 als Regulator von NF-kB vor, und stellt damit einen neuen Ansatz für Therapieentwicklung. Mehr Forschung ist dennoch erforderlich, um den biologischen Kontext und die genaue Kinetik der Regulation zu definieren.
Keywords: lung cancer; NF-kB signalling; MTA2; ddc:610